Hashtag bioethics - Banerjee, Mohini (The Hastings Center report, 2014)
When I first started at the Center, I approached our public affairs and communications manager to see if I could help bolster our Twitter presence. I saw social media as having a potential to reach people in a way academic papers and conferences never could. My own desire to see knowledge of bioethical issues seep into the general public's consciousness fueled this optimistic view. Twitter seemed to be an especially effective method of widening the reach of bioethics. It would help create a wider Hastings Center community by spreading knowledge and creating a new forum for discussion. But Twitter has its limits. I believe new media provides more fluid ways of communicating, but can 140 characters inspire anyone to read and think more about the value of a family's wishes against the costs of keeping a legally dead person on a ventilator?